Penggunaan Media Flashcard Berbasis Augmented Reality Pada Materi Ragam Budaya Indonesia Untuk Menanamkan Nilai Kewargaan Siswa Gen Alpha - Hamidah, Itsnani Nur; Nurfadillah, Dilla; Caniago, Renaldo; Yadi, Dede; Zulfitria, Zulfitria (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Augmented Reality (AR) is a technology used to bring the virtual world into the real world simultaneously. Augmented Reality (AR)-based flashcard learning media is used as an alternative solution to problems in learning about the diversity of Indonesian culture, particularly traditional houses. The purpose of this study is to provide an in-depth description of Generation Alpha students' experiences in using AR-based flashcards. This media can transform images of traditional houses on flashcards into 3D objects, making the learning method less monotonous and encouraging students to explore the topic more deeply. Through this deeper understanding, students can internalize civic values such as patriotism, which is reflected in their appreciation of cultural diversity, as well as a sense of pride and respect for culture.